The Relationship Between Knowledge And Attitude Of Adolescent Girls With Personal Hygiene Behavior During Menstruation - Niar, Niar; Sartika, Sartika; M, Syikir; Firna, Fransiska (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Personal hygiene is an effort in maintaining and caring for the cleanliness of all members of the body including reproductive organs. During menstruation, the blood vessels in the uterus are easily injured, therefore personal hygiene is very important to be carried out in order to be free from reproductive organ dysfunction. (Sri Ninta, 2023). Objective: To determine the relationship between knowledge and attitude of adolescent girls with personal hygiene behavior during menstruation at Mts Fathul Amin Matakali. Method: The type of research used is quantitative research with the research design that the author makes is an Analytical Survey using a Cross Sectional study approach. The population in this study were all adolescent girls of Mts Fathul Amin Matakali who had experienced menstruation as many as 50 female students. the sampling technique used was non probability with the type of sampling, namely total sampling. The research instrument is a questionnaire. This research questionnaire sheet consists of questions regarding knowledge, attitudes with personal hygiene behavior during menstruation which are distributed directly by researchers to respondents or by interviews between researchers and respondents. Data analysis using Chi Square analysis. Result: There is a relationship between knowledge and personal hygiene behavior in adolescent girls at Mts Fathul Amin Matakali with a p-value = 0.004 (<0.05). There is a relationship between attitude and personal hygiene behavior in adolescent girls at Mts Fathul Amin Matakali with a p-value = 0.000 (<0.05). Conclusion: Knowledge and attitude show that there is a relationship with personal hygiene behavior during menstruation at Mts Fathul Amin Matakali. Mts Fathul Amin Matakali can utilize print media such as posters, leaflets, or school magazines to increase the exposure of female students to information about personal hygiene during menstruation.